ETHNOCHEMISTRY: ANALISIS RELEVANSI MATERI SISTEM PERIODIK UNSUR DENGAN KEARIFAN LOKAL SASAK: ETHNOCHEMISTRY: MATERIAL RELEVANCE ANALYSIS OF THE PERIODIC SYSTEM OF ELEMENTS WITH SASAK LOCAL WISDOM - Dwi Wahyudiati (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2021)
This study aims to analyze the relevance of the periodic table of elements (SPU) material with local Sasak wisdom which has potential as a source of learning chemistry. The type of research used is descriptive qualitative through data collection techniques, namely interviews, observation, and documentation. The data obtained from observations, interviews, and documentation were analyzed using Miles & Huberman's qualitative analysis technique. The results showed that in the tradition of the Sasak people, lead (Pb) as an example of an element of group IVA and iron (Fe) which is group VIB and located in period 4 are widely used in the daily life of the Sasak people as an ingredient in making traditional musical instruments (terumpang, gongs, oncer or petuk, kenceng, and rencek), tools for traditional ceremonies, religious ceremonies, and traditional arts. In addition to iron (Fe), several types of elements such as gold (Au), silver (Ag), copper (Cu) which occupies group IB, and elements of zinc (Zn) which are in group IIB. These elements are widely used because they are related to the physical and chemical properties of these elements, namely easy to forge, not easy to rust, easy to find in everyday life, and not reactive. The conclusion of the study is that there is a relevance of the material on the periodic system of elements with local Sasak wisdom, namely on the sub-subject of the periodic classification of elements and the diversity of elemental properties. Recommendations for further research need to be researched to develop teaching materials for chemistry integrated with Sasak local wisdom as a form of implementation in learning. Penelitian ini bertujuan menganalisis relevansi materi sistem periodik unsur (SPU) dengan kearifan lokal Sasak yang memiliki potensi sebagai salah satu sumber belajar kimia. Jenis penelitian yang digunakan yaitu deskriptif kualitatif melalui teknik pengumpulan data yaitu wawancara, observasi, dan dokumentasi. Data hasil observasi, wawancara, dan dokumentasi yang diperoleh dianalisis menggunakan teknik analisis kualitatif Miles & Huberman. Hasil penelitian menunjukkan bahwa dalam tradisi masyarakat Sasak, timbal (Pb) sebagai salah satu contoh unsur golongan IVA dan besi (Fe) yang merupakan golongan VIB dan terletak periode 4 banyak dimanfaatkan dalam kehidupan sehari-hari masyarakat Sasak bahan dalam membuat alat-alat musik tradisional (terumpang, gong, oncer atau petuk, kenceng, dan rencek), alat-alat untuk upacara adat, upacara keagamaan, maupun kesenian tradisional. Selain besi (Fe), beberapa jenis unsur seperti emas (Au), perak (Ag), tembaga (Cu) yang menempati golongan IB, dan unsur seng (Zn) yang berada pada golongan IIB. Unsur-unsur tersebut banyak dimanfaatkan karena berkaitan dengan sifat fisika dan sifat kimia unsur-unsur tersebut yaitu mudah ditempa, tidak mudah berkarat, mudah ditemukan dalam kehidupan sehari-hari, dan tidak bersifat reaktif. Kesimpulan penelitian yaitu terdapat relevansi materi sistem periodik unsur dengan kearifan lokal Sasak yaitu pada sub pokok bahasan penggolongan periodik unsur dan keragaman sifat unsur. Rekomendasi untuk penelitian selanjutnya perlu dilakukan penelitian untuk mengembangkan bahan ajar kimia terintegrasi kearifan lokal Sasak sebagai bentuk implementasi dalam pembelajaran.